2013
DOI: 10.1016/j.cell.2013.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Contact Permits Transcription between Coregulated Genes

Abstract: Transcription of coregulated genes occurs in the context of long-range chromosomal contacts that form multigene complexes. Such contacts and transcription are lost in knockout studies of transcription factors and structural chromatin proteins. To ask whether chromosomal contacts are required for cotranscription in multigene complexes, we devised a strategy using TALENs to cleave and disrupt gene loops in a well-characterized multigene complex. Monitoring this disruption using RNA FISH and immunofluorescence mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
167
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(182 citation statements)
references
References 49 publications
(97 reference statements)
11
167
0
Order By: Relevance
“…This observation is consistent with previous statistical analysis, indicating that coregulated genes tend to cluster, and genes that are physically proximal tend to coexpress (21,31,32). Coactivated genes can also form "transcription factories" or "multigene complexes" in higher eukaryotic species (33,34), so our findings here are likely to be one example of a more general phenomenon. This result can also explain why there have been conflicting observations on homologous pairing in yeast (12)(13)(14)(15): The experimental outcome likely depends on the inspected regions and their transcription status.…”
Section: Discussionsupporting
confidence: 92%
“…This observation is consistent with previous statistical analysis, indicating that coregulated genes tend to cluster, and genes that are physically proximal tend to coexpress (21,31,32). Coactivated genes can also form "transcription factories" or "multigene complexes" in higher eukaryotic species (33,34), so our findings here are likely to be one example of a more general phenomenon. This result can also explain why there have been conflicting observations on homologous pairing in yeast (12)(13)(14)(15): The experimental outcome likely depends on the inspected regions and their transcription status.…”
Section: Discussionsupporting
confidence: 92%
“…These microenvironments are characterized by high concentrations of transcription factors that can potentiate the induction of target genes (Mir et al, 2017;Tsai et al, 2017). The localization of genes to accumulations of transcription factors (Papantonis et al, 2012;Liu et al, 2014) might also explain observations of proximity-based gene regulation (Fanucchi et al, 2013). Our work explains how transcription establishes microenvironments that can retain several transcribed genes and potentially facilitate the accumulation of transcription factors.…”
Section: Microenvironments Might Be Hubs Of Gene Regulationmentioning
confidence: 63%
“…45 Recently, we developed a novel single cell microscopy-based assay, to address the role of loop-mediated contact on transcription of interacting genes in the SAMD4A/TNFAIP2/SLC6A5 multigene complex. 46 In the assay, TALE nucleases (TALENs) were used to induce a DSB at the approximate site within each of these three gene loops that was established by 3C-technologies to engage in contact. 4,46 We have also tested the ability of other site-specific nucleases to disrupt the SAMD4A gene loop (Fig.…”
Section: What Are the Rules Governingmentioning
confidence: 99%
“…34 Consistent with previous studies, 4 co-localization between the FISH foci of these three genes was only observed at a low percentage of all alleles across the population (~5%). 46 This would suggest that this small fraction of the population represents a "special pool" of primed cells that permit loop-mediated contact.…”
Section: What Are the Rules Governingmentioning
confidence: 99%
See 1 more Smart Citation